Evolution driven by a varying host environment selects for distinct HIV-1 entry phenotypes and other informative variants - Zhou, Shuntai; Long, Nathan; Swanstrom, Ronald (Frontiers in Virology, 2023)
HIV-1 generates remarkable intra-and inter-host viral diversity during infection. In response to dynamic selective pressures of the host environment, HIV-1 will evolve distinct phenotypes -biological features that provide fitness advantages. The transmitted form of HIV-1 has been shown to require a high density of CD4 on the target cell surface (as found on CD4+ T cells) and typically uses CCR5 as a co-receptor during entry. This phenotype is referred to as R5 T cell-tropic (or R5 T-tropic); however, HIV-1 can switch to a secondary co-receptor, CXCR4, resulting in a X4 T cell-tropic phenotype. Macrophage-tropic (or M-tropic) HIV-1 can evolve to efficiently enter cells expressing low densities of CD4 on their surface (such as macrophages/microglia). So far only CCR5-using M-tropic viruses have been found. M-tropic HIV-1 is most frequently found within the central nervous system, and infection of the CNS has been associated with neurological impairment. It has been shown that interferon resistance phenotypes have a selective advantage during transmission, but the underlying mechanism of this is still unclear. During untreated infection, HIV-1 evolves under selective pressure from both the humoral/antibody response and CD8+ T cell killing.Sufficiently potent antiviral therapy will suppress viral replication, but if the antiviral drugs are not sufficiently potent to stop replication then the replicating virus will evolve drug resistance. HIV-1 phenotypes are highly relevant to treatment efforts, clinical outcomes, vaccine studies, and cure strategies. Therefore, it is critical to understand the dynamics of the host environment that drive these phenotypes and how they affect HIV-1 pathogenesis. This review will provide a comprehensive discussion of HIV-1 entry,